2015
DOI: 10.1515/acve-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Blood Gases, Acid-Base Status And Plasma Lactate Concentrations In Calves With Respiratory Diseases

Abstract: The purpose of this study was to evaluate in calves the effects of respiratory diseases of various severities on blood gases, acid-base balance and plasma lactate concentration. We included in the study 128 calves with clinical signs of various severities and outcomes of respiratory disorders. The age of the calves ranged from 1 to 12 months. According to the clinical fi ndings, course of the disease and time of blood collection, the sick calves were divided into three groups: RD 1 (n=34) -calves with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(26 reference statements)
0
6
2
Order By: Relevance
“…12 It is difficult to compare our results with those of other studies because the latter were performed using experimental inoculation 8,10 or calves with chronic BP often affected by lifethreatening conditions. 33,34 The discrepancy between our results and those of other previously published studies could be attributed to the disparity in the nature and distribution of lung lesions induced by the experimental inoculation of the pathogens and the chronic conditions of the disease. For example, the inoculation of the respiratory syncytial virus caused lesions in approximately 24% of the lung mass, which severely affected gas exchanges during the acute phase of the postinfection disease.…”
Section: Categorizationscontrasting
confidence: 90%
“…12 It is difficult to compare our results with those of other studies because the latter were performed using experimental inoculation 8,10 or calves with chronic BP often affected by lifethreatening conditions. 33,34 The discrepancy between our results and those of other previously published studies could be attributed to the disparity in the nature and distribution of lung lesions induced by the experimental inoculation of the pathogens and the chronic conditions of the disease. For example, the inoculation of the respiratory syncytial virus caused lesions in approximately 24% of the lung mass, which severely affected gas exchanges during the acute phase of the postinfection disease.…”
Section: Categorizationscontrasting
confidence: 90%
“…About half of the calves with severe respiratory syndrome had indicators of partial pressure of oxygen and saturation of hemoglobin with oxygen common to venous blood. Meanwhile, an increase in pCO 2 values was reported only in calves with severe clinical symptoms [30]. Calves with severe clinical symptoms of BRD were not included in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Our study found a significant decrease in pO 2 and an increase in pCO 2 values by 15.7% and 34.1% (P < 0.05), respectively, in venous blood in calves with respiratory failure (group I) compared to healthy animals (group II). Šoltésová et al [30] described the highly correlated severity of respiratory diseases and the values of oxygen partial pressure and hemoglobin oxygen saturation. Changes that were noted in calves with the disease were compared with the clinical picture, reducing the values even in mild cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate measurement in horses is predictive of mortality in sick neonates (Borchers et al 2012 ; Corley, Donaldson & Furr 2005 ; Henderson et al 2008 ) and adult emergencies (Delesalle et al 2007 ; Furr, Lessard & White 1995 ; Johnston, Holcombe & Hauptman 2007 ; Schulman, Nurton & Guthrie 2012 ; Tennent-Brown et al 2010 ). In bovine medicine, lactate can be useful as a prognostic indicator in cattle with respiratory disease (Coghe et al 2000 ; Helena et al 2015 ) and abomasal disorders (Buczinski, Boulay & Francoz 2015 ; Figueiredo et al 2008 ). In dogs, lactate measurement has prognostic value in systemically ill animals (Lagutchik et al 1998 ; Stevenson et al 2007b ), dogs with hypotension (Ateca, Dombrowski & Silverstein 2015 ), septic peritonitis (Cortellini, Seth & Kellett-Gregory 2014 ) and babesiosis (Nel et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%